Micro and macro determinants of health: Older immigrants in Europe - Amelie F. Constant; Teresa M. García-Mu\~noz; Shoshana Neuman; Tzahi Neuman (Institute for the Study of Labor (IZA), 2014)
We study the health determinants of immigrant men and women over the age of fifty, in Europe, and compare them to natives. We utilize the unique Survey of Health Aging and Retirement (SHARE) and augmented it with macroeconomic information on the 22 home countries and 16 host countries. Using Multilevel Analysis we can best capture the within and between countries variation and produce reliable results. We find that during the first decade after arrival, immigrants report higher levels of subjective health compared to natives and to previous cohorts of immigrants. As time since migration passes by, reported subjective health decreases; immigrants' health becomes the same as that of comparable natives or it even decreases. The level of economic development of both the origin and the host country positively affect the individual's health, but the effect of the host country is much more pronounced. It appears that positive and negative deviations (of the host from the origin country) have different impacts on individual health: an increase in a positive deviation (the country of origin is more developed compared to the host country - a 'loss' for the immigrating individual) leads to a decrease in the immigrant's subjective health, while an increase in the absolute negative deviation (a 'gain' for the immigrating person) leads to an increase in the immigrant's subjective health. These differential effects can be explained as some variant of the Loss-Aversion Theory.
Keywords: C22; J11; J12; J14; O12; O15; O52; 330; self-assessed health status; immigration; Europe; country of origin; older population; multilevel regression